Poetry and the question of modernity from Heidegger to the present - Cooper, Ian 1979- (Routledge, 2020)
Note on Translations -- Introduction: Poetry, philosophy, and modernity: Germany and beyond -- Chapter One: Clearings: Finitude, historicity, and the space of poetry -- Chapter Two: Straitenings: Paul Celan and world disclosure -- Chapter Three: Lightenings: The shades of redress -- Chapter Four: Earthings: Enlightenment, religion, and the poem of modernity
Includes bibliographical references and index
Keywords: Celan, Paul -- 1920-1970; Hölderlin, Friedrich -- 1770-1843; Heidegger, Martin -- 1889-1976; Lyrik; Hermeneutik; Modernität; Heidegger, Martin / 1889-1976 / Knowledge / Poetry; Celan, Paul / Criticism and interpretation; Murray, Les A / 1938-2019 / Criticism and interpretation; Heaney, Seamus / 1939-2013 / Criticism and interpretation; Religion and poetry; Poetry / Philosophy; Poetry, Modern / History and criticism; Transcendence (Philosophy)